PENYUSUNAN ANGGARAN PERSPEKTIF FIQHI ANGGARAN HUKUM EKONOMI SYARIAH - Arno, Abdul Kadir (Al-Amwal : Journal of Islamic Economic Law, 2016)
In managing the budget, honesty (shidq) is a liability, which can?t be executed unless the application of the principle of budget transparency. Therefore, based on the rules then, do the transparency of the budget is mandatory. In the view of Islam, avoiding the transparency of the budget is disobedience. The application of the basic values of Islamic law in the preparation of the budget becomes extremely important in anticipating the leak. In this context the existence of fiqh budget is very urgent, because it is not just for the sake of personal interest but also the public. Therefore the parties involved in the preparation of the budget should be linked by law, so that the consequences of which can be accounted for before the courts in case of fraud